Community Legal Awareness of Ownership of Land Title Certificates in Kanagarian Siguntur Muda, Koto Xl Tarusan District, South Coast Regency - Ratna Delina; Indra Rahmat; Jamurin Jamurin (CV. Rayyan Dwi Bharata, 2022)
This research is backgrounded first to find out how the community's legal awareness of the importance of registering property rights to land, and secondly to find out the factors that prevent people from registering property rights to land. The type of research used is qualitative research, which is to describe the situation as it is. Data collection techniques use interview, observation and documentation techniques. The data analysis techniques used are data reduction, data presentation as well as verification and conclusions. The results showed that the inhibiting factors of the community in managing land title certificates: a) Economic factors, costs are certainly obstacles in making land rights certificates, especially for communities that are lacking in economic terms. b) Low level of education, lack of public awareness of the law stemming from the lack of public education coupled with lack of socialization by the local government. c) The lack of interest of the community to certify the land, the lack of desire of the community is also a factor inhibiting the community itself from registering its land.